Protecting More Than Just Books: A Curricula Study of Traditional Cultural Expression in U.S. LIS Programs - Cheng, Siyao; Ocepek, Melissa; Benson, Sara (Journal of Copyright in Education & Librarianship, 2024)
More and more, librarians’ day-to-day job responsibilities include working with Traditional Cultural Expressions (TCEs) and their divergent needs. Nevertheless, TCEs—and their specialized care—lack adequate attention and appropriate training in Library and Information Science (LIS) pedagogy. This indicates that LIS students may be less prepared to ethically work on TCE-related inquiries in the future. This study conducts a curricula content analysis of 35 ALA-accredited Master of Library and Information Science (MSLIS) programs to preliminarily assess the current state of TCE-related topics represented in LIS programs. Through investigating course descriptions, the research evaluates the depth and breadth to which LIS students’ coursework incorporates topics related to TCEs and their care. The synthesized findings demonstrate that only a small number of LIS programs even offer TCE-centric courses; of these, very few programs explicitly require students to take them. Failure to integrate TCEs into the core curriculum results in students being unprepared for the corresponding challenges in their prospective workplaces, especially as most TCEs are not covered by copyright law. The implication of this study could be a fruitful and rigorous invitation for LIS educators to revise their LIS curriculum to keep pace with the ever-evolving information needs that arise in contemporary library contexts for diverse populations.